On the Reidemeister torsion of rational homology spheres - Liviu I. Nicolaescu (International Journal of Mathematics and Mathematical Sciences)
We prove that the Modℤ reduction of the Reidemeister torsion of a rational homology 3-sphere is naturally a ℚ/ℤ-valued quadratic function uniquely determined by a ℚ/ℤ-constant and the linking form.